2018
DOI: 10.30877/ijmh.6.1.2019.56-61
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Dimensions of Obsessive-Compulsive Disorder and Family Accommodation: OCD severity and Family Accommodation

Abstract: Background and Objectives: Family accommodation (FA) refers to ways in which family members assist the patient in the performance of rituals, compulsions, avoidance of anxiety provoking situations, or modification of daily routines to assist a relative with obsessive-compulsive disorder. The purpose of this study was to study the association between the family accommodation and dimensions of obsessivecompulsive disorder (OCD). Methods: The study was included 45patients and their family members, Yale brown Obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…In the present study, the mean age of the patients was found to be 32.04 (9.41) years, and most patients were female and married, which is similar to other studies conducted in this geographical region 22 23. The mean age of onset of illness was 25.75 (8.55) years, as seen in other studies 22 24. Among the psychiatric comorbidities, depression was found to be the most common (23.21%), a finding that is consistent with other studies 24 25.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the mean age of the patients was found to be 32.04 (9.41) years, and most patients were female and married, which is similar to other studies conducted in this geographical region 22 23. The mean age of onset of illness was 25.75 (8.55) years, as seen in other studies 22 24. Among the psychiatric comorbidities, depression was found to be the most common (23.21%), a finding that is consistent with other studies 24 25.…”
Section: Discussionsupporting
confidence: 91%
“…This variation may be due to comparatively smaller sample size and stringent selection criteria in our study. An Indian study reported a mean Y-BOCS score of 25.86 (8.07), which was similar to that of our study 22…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, explorative analysis showed a positive relationship between the OCD subtypes contamination and symmetry and family accommodation. This is in line with research that repeatedly found family accommodation to be associated with contamination symptoms (Boeding et al, 2013;Shrinivasa et al, 2020;Verma, Mahour, Dalal, & Agarwal, 2019). We hypothesize that contamination obsessions and compulsions are particularly well-suited for accommodation, because they are overt, often highly impairing, strongly disturbing family functioning and possibly easier to understand and relate to.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies investigating the relationship between FA and symptom dimensions showed that family members present higher FA scores on cleaning/contamination symptoms (Albert et al, 2010; S. Evelyn Stewart et al, 2008; Verma et al, 2019). One study found no association between FA and OCD symptom dimensions (Gomes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%